The Impact of Environmental Factors on International Accounting: An Exploratory Study of Factors Affecting the Development of the Accounting Model in the Iraqi Environment (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2026)
The research aims to study the environmental variables influencing the development of international accounting systems. It seeks to explain the impact of social values on accounting values and the effect of environmental factors on the development of the accounting model in the Iraqi context. The research employs an inductive approach in presenting its theoretical framework and utilizes an empirical reasoning methodology in its applied aspect, employing data analysis techniques using a questionnaire. The research reached several conclusions, the most important of which is the diversity of environmental factors and the varying degrees of their influence on the accounting model across different countries. These factors have yielded four distinct and comparative models for the development of accounting at the international level: the macroeconomic model, the microeconomic model, the knowledge-independent model, and the unified accounting model. The results of the applied aspect also indicate that different environmental factors have varying impacts on the development of the accounting model in the Iraqi context. Specifically, the results suggest that the nature of capital markets, the political system, and economic growth have the most significant influences, respectively. Based on the findings, the research presented a set of recommendations, the most important of which is raising academic and professional awareness of the importance of local environmental factors, studying them thoroughly, and taking them into account when developing an appropriate accounting model. It also emphasized the need for further research focused on examining the similarities and differences between local and international environmental factors, and on developing generalizations and predictions regarding the expected development of the accounting model.